Knowledge Level of Patients Related to Gastritis Chronic Prevention in The Work Area of Mangulewa Public Health Center - Rosalina Lepu; Indriati A. Tedju Hinga; Yuliana Radja Riwu (Universitas Nusa Cendana, 2022)
Gastritis is inflammation of the stomach wall that occurs due to irritation and infection. Gastritis is attributed to the decline in gastric function and may lead to gastric cancer and death. Knowledge of the causes and processes of gastritis can encourage efforts to prevent gastritis. This study aims to describe the level of patient knowledge in efforts to prevent chronic gastritis in the work area of Mangulewa Public Health Center (PHC) in 2021. The type of research used was descriptive quantitative research. The population in this study were all gastritis patients with the age category of 25-44 years. The sample consisted of 32 people selected by using total sampling technique. The results showed that most of the respondents had good knowledge about chronic gastritis (68.7%) and did not take preventive measures (90.6%). The PHC needs to increase promotive and preventive efforts for chronic gastritis in the community.